Bianchi Type-VI0 Cosmological Model with Special Form of Scale Factor in Sen-Dunn Theory of Gravitation - Basumatay, D.; Dewri, M. (Journal of Scientific Research, 2021)
A Bianchi Type-VI0 cosmological model with a special form of scale factor is studied. Einstein field equations in Sen-Dunn theory are obtained and solved for exact solutions. This solution gives a scenario of the dark energy model which tends to a ɅCDM model. The physical and geometrical properties are also obtained and analyzed with the present day observations.